KOREYS VA OʻZBEK TILIDA HURMAT DARAJALARI QIYOSIY TAHLILI - Xolmurodova Nigora Faxriddinovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
This article analyzes the features of the expression of the category of respect in the Korean and Uzbek languages. In both languages, the concept of respect is considered an important sociolinguistic phenomenon, and its manifestation through linguistic units and cultural factors is highlighted. In Korean, the category of respect is expressed through a complex system - 다임법, which is characterized by its formation on the basis of speech levels (존댓말 and 반말), grammatical suffixes, special lexical units, and social hierarchy. In Uzbek, the category of respect has a relatively simple but stable system, which is expressed mainly through personal pronouns (sen/siz), verb forms (-siz, -lar), lexical means (ustoz, opa, janob, etc.), as well as speech style and intonation. In both languages, the category of respect is used in direct dependence on age, social status, and communication situation. The results of the study show that while respect in Korean is grammatically and lexically deeply systematized, in Uzbek it is expressed more through stylistic and lexical means. Nevertheless, a common aspect for both languages ​​is the inextricable connection of respect with national culture, morality, and social values.